Age-related Effects of Gastroduodenoscopy on Arterial Oxygen Saturation - Nishiyama, Katsuhito; Kinoshita, Yoshikazu; Kitajima, Naoto; Ito, Toshio; Fukuzaki, Hisashi; Chiba, Tsutomu; Inatome, Tetsuya (Nihon Rōnen Igakkai zasshi, 1992)
Although endoscopy is widely used for safe and accurate examinations of gastroduodenal disease cases, several investigators reported arterial oxygen desaturation occurring during endoscopy. Endoscopy-induced oxygen desaturation is hazardous because it increases the risk of cardiac arrhythmia. This study is designed to investigate whether gastroduodenal endoscopy causes remarkable oxygen desaturation in elderly patients in comparison with younger ones and to study whether nasal oxygen administration can prevent it. Forty-four patients over 61 years old and 37 patients younger than 60 were divided into two groups, to one of which 100% oxygen (2l/min) was administerd through nasal prongs. During endoscopy, blood pressure, pulse rate, and arterial oxygen saturation (SaO2) were recorded at one-monute intervals by a pulse oximeter. Intubation of the endoscope caused a transient drop in oxygen saturation both younger and older patients with greater drops in older subjects (1.7±0.4% in the young and 3.3±0.8% in the old groups). In the older groups, two out of 20 patients who had no oxygen administration showed a saturation decrease of over 7%. On the other hand, no younger subject showed such a large degree of oxygen desaturation. Oxygen administration effectively prevented the endoscopy-induced desaturation both in younger and in older patients. In summary, the results of this study suggested that older subjects had a greater decrease of oxygen saturation during gastroduodenofiberscopy and that oxygen administration is useful to prevent the endoscopy-induced desaturation.